PENDIDIKAN KLINIK SEBAGAI INSTRUMEN PENTING DALAM PEMBAHARUAN PENDIDIKAN HUKUM DI INDONESIA - Siregar, Sahnan Sahuri; Rosadi, Otong (UNES Journal of Swara Justisia, 2020)
The field of legal science as an applied science should have given birth to law graduates ready for combat to engage in the world of law in particular and community development in general. Be it as a lawyer, judge, prosecutor, notary, legal consultant as well as other legal professions. As one of the "important instruments" that should be present in the study of legal science is the legal clinic. The legal clinic is present with the intention of equipping law school students about practical knowledge, skills, and values ​​in order to realize legal and justice services that are carried out with interactive and reflective teaching methods. The presence of a legal clinic in the legal science curriculum has the least important role in the effort: the implementation of the Tri Dharma of Higher Education; Increasing student competence in law; and as a medium for the public to gain access to justice. The author suggests updating the legal science curriculum, through Legal Clinic Education.